APPLICATION OF ACCOUNTING INFORMATION SYSTEM IN IMPROVING FINANCIAL MANAGEMENT EFFICIENCY IN MSME ASSOCIATIONS - Dimas Arya Winata; Suwandi Suwandi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study investigates how the application of Accounting Information Systems (SIA) enhances financial management efficiency in Micro, Small, and Medium Enterprises (MSMEs). Recognizing the challenges faced by MSMEs in managing finances, the research emphasizes the role of information technology in supporting more effective and transparent accounting processes. Methods: Using a qualitative case study approach involving several MSME associations that have adopted SIA, data was collected through interviews, observations, and document analysis. Results: The findings reveal that implementing SIA positively impacts financial management by automating transaction recording, improving data accuracy, and accelerating reporting. Additionally, SIA facilitates better decision-making by providing timely and relevant financial information. Based on these results, the study recommends that MSME associations integrate SIA into their management systems to boost business performance and competitiveness. Keywords: Accounting Information System, Financial Efficiency, Improved Financial Performance UMKM